Zootechnologies A Media History of Swarm Research - Vehlken, Sebastian (Amsterdam University Press, 2019)
Swarming has become a fundamental cultural technique related to dynamic processes and an effective metaphor for the collaborative efforts of society. This book examines the media history of swarm research and its significance to current socio-technological processes. It shows that the hype about collective intelligence is based on a reciprocal computerization of biology and biologization of computer science: After decades of painstaking biological observations in the ocean, experiments in aquariums, and mathematical model-making, it was swarms-inspired computer simulation which provided biological researchers with enduring knowledge about animal collectives. At the same time, a turn to biological principles of self-organization made it possible to adapt to unclearly delineated sets of problems and clarify the operation of opaque systems - from logistics to architecture, or from crowd control to robot collectives. As zootechnologies, swarms offer performative, synthetic, and approximate solutions in cases where analytical approaches are doomed to fail.